Integration of amide proton transfer-weighted imaging and methionine positron emission tomography histogram parameters enhances the prediction of isocitrate dehydrogenase mutations in adult diffuse gliomas - Masaoki Kusunoki; Takuro Isoda; Koji Yamashita; Yoshiyuki Kitamura; Kazufumi Kikuchi; Motohiro Sando; Shingo Baba; Daisuke Kuga; Yutaka Fujioka; Fumiya Narutomi; Koji Yoshimoto; Kousei Ishigami; et al. (EJNMMI Reports)
Abstract Background To evaluate whether the combination of amide proton transfer-weighted imaging (APT-WI) and methionine positron emission tomography (MET-PET) enhances the non-invasive prediction of isocitrate dehydrogenase (IDH) mutation status in adult diffuse gliomas. Results We retrospectively analysed 28 adult patients with histologically confirmed diffuse gliomas who underwent preoperative APT-WI and MET-PET imaging at our institution. Histogram analyses were conducted for both imaging modalities, extracting parameters such as the 10th, 50th, 70th, and 90th percentiles, mean, variance, skewness, and kurtosis. Parameters between IDH-mutant and IDH-wildtype gliomas were compared using the Mann–Whitney U test. Diagnostic performance was assessed using receiver operating characteristic (ROC) curve analysis, and combined models of the two parameters were constructed using multivariable logistic regression. IDH-wildtype gliomas exhibited significantly higher APT-WI 90th percentile (APT90) values (median: 3.51%, interquartile range [IQR]: 1.92–4.23%) compared to IDH-mutant gliomas (median: 2.24%, IQR: 1.52–2.85%, p = 0.039). Similarly, IDH-wildtype gliomas showed elevated MET-PET maximum tumour-to-normal ratios (TNRmax) (median: 2.51, IQR: 2.13–3.41) compared to IDH-mutant gliomas (median: 1.62, IQR: 1.30–2.77, p = 0.020). ROC curve analysis indicated that the combined model of APT90 and TNR kurtosis achieved an area under the curve of 0.85, demonstrating superior diagnostic accuracy compared to that of single-parameter models. Conclusions Combining histogram-derived parameters from APT-WI and MET-PET significantly improves the diagnostic accuracy for predicting IDH mutation status in diffuse gliomas. This non-invasive approach may serve as a valuable adjunct for preoperative evaluation and the development of personalised treatment strategies in patients with gliomas.